Pengaruh Service Excellence Training Bagi Staf Administrasi BAAK Politeknik Negeri Semarang Terhadap Service Excellence Skill - Puswiartika, Dhevy (Tri Sentra Jurnal Ilmu Pendidikan, 2013)
This research intended to understand the effect of service excellence training for administrative staffs of BAAK Politeknik X to service excellence skill. The number of participants who attented training were 8 administrative staffs. The results showed that service excellence training have a significant effect to service excellence skill. There was a difference between service excellence skill before and after service excellence training for administrative staffs of BAAK Politeknik X.Â  This conclusion based on the z value = - 2,598 (p=0,009 ; p<0,05 ). Service excellence skill after service excellence training was higher than service excellence skill before service excellence training.